Fabrication of PS/PMMA/MgO Nano Composites: Structural and Optical Properties as Coating Materials for Antibacterial Applications - Ahmed A. Auda (Journal of Global Pharma Technology, 2016)
Optical properties of P.S.P.M.M.A. polymer composite with doped MgO nanoparticles have been studied. The composite study was prepared by the solution of casting. Various concentrations were used for polymer material P.S- P.M.M.A/ (75 %-25 %). The weight ratios for Nano material (MgO) were 0 %, 2 %, 4% and 6 % of the total weight for the 1g sample. The optical spectrometers were measured at a wavelength of 220 nm-890 nm using a FTIR device optical properties of PS such  as  absorbance,  transmittance, absorption  coefficient, refractive  index,  extinction  coefficient,  real   and  imaginary  parts  of dielectric constant have been investigated. The results of the test on the refractive index, the attenuation coefficient and the insulation constant in its real and imaginary parts give good results with increasing the concentration of nanoparticles. The composite materials of polymer and nanoparticles were applied as antibacterial to Pseudomonas bacteria and they give the concentration (0.02 and 0.04 MgO) a good effectiveness to those bacteria.Keywords: Optical properties, Polystyrene, PMMA, Pseudomonas Bacteria.